PENGARUH KUALITAS LAYANAN DAN FASILITAS TERHADAP LOYALITAS PENUMPANG PADA PELABUHAN DOMESTIK SEKUPANG - Fitriyani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this study was to determine the effect of service and facility quality on passenger loyalty at Sekupang domestic port uslng the slovin sampIing technique with an error margin of 5% from 257,835 passengers so as to produce 400 respondents who were passengers at the domestic port of Sekupang. Data collection methods are questionnaires. The data quaIity test ln this study used the vaIldlty and reIiabiIty test, the cIassic assumptlon test and the effect test ln thls study used muItiple Iinear regresslon analysls and the coefflclent of deternation anaIysis ), whiIe the hypothesls test ln thls study used (t test) and (F test) uslng SPSS software program verslon 21. The results of the coefficient of determinatlon obtalned from the service and facility quality varlables have a efect of 73.3% on passenger loyaIty. The resuIts of muItlple Ilnear regresslon tests showed that service quality (X1) had an efect of 20.3% on passenger loyalty (Y) and facilities (X2) had an efect of 35.3% on passenger loyalty (Y). From the resuIts of the t test and F test, it can be concIuded that the service quality has a partially significant efect on passenger loyaIti and the falility has a partially signilificant efect on passenger loyalty, and the quaIlty of service and facilitiies together has a significant simultaneous efect on pasenger loyalty at the Domestic Port Sekupang.